Wounded stories. - Stokes, Patrick (New Philosopher, 2022)
In some corners of the internet, you'll find people sharing and comparing photos of their "bug-out bags". But there's also a very human vulnerability: our inability to foresee the sorts of abrupt events that change our whole lives instantly. These are backpacks or duffle bags stuffed full of things their owners believe they'll need in an emergency, from water and bandages to flares and gas masks.